AGLOMERASI DAN PERTUMBUHAN PRODUKTIVITAS INDUSTRI MANUFAKTUR INDONESIA PERIODE 2008-2012 - Agnes Wijaya; Suyanto Suyanto; Firman Rosjadi Djoemadi (Perpustakaan Universitas Surabaya, 2018)
This study examines the effect of agglomeration economies on productivity growth in Indonesian manufacturing industries for the period of 2008-2012. Productivity growth is measured by using Fare-Primont Productivity Index. The firm productivity growth is regressed against two types of agglomeration: specialisation and diversity. Then, it is also regressed against set of firm and industry characteristic variables : size,ownership, industry concentration, firm exit and firm entry. The results show that specialisation affects the industry positively while negative effect is encountered for diversity to the aggregate manufacturing industry.